Pengaruh Pembiayaan Mikro Syariah Dalam Mengembangkan Usaha Di Kabupaten Lebak - Maskur Maskur; budiman budiman (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2019)
This research is motivated by the fundamental problem of Islamic banking which has an important role in the development of the community's economy in financing the microeconomic sector, banks have demands to pay attention to the small business sector, especially related to financial limitations. in developing micro businesses of independent Islamic bank customers in Lebak district, the problem formulation in this study is as follows: (1) What is the mechanism of sharia microfinance applied by Bank Syariah Mandiri, (2) What is the concept of Akad used in microfinance at Bank Syariah Mandiri, (3) How is the implementation of microfinance in helping to develop micro businesses in Lebak district? The purpose of this research is to find out and describe microfinance, and find out how the contracts used in sharia microfinance, and to find out the implementation of microfinance in developing micro businesses of Bank Syariah Mandiri customers in Lebak Regency. This research uses quantitative research methods with a quantitative descriptive analysis approach, then from 58.8% because the selling price (poko + margin) offered is quite light, 23.4% think otherwise. 43.4% felt that there was no capital solution in microfinance and 56.6% stated that microfinance really provided capital solutions for micro, small businesses. 36.6% stated that microfinance makes it difficult for them to do business, and 63.4% stated that microfinance does not make it difficult at all. Then 53.4% stated that microfinance at independent Islamic banks had elements of usury, and 46.6% stated that microfinance at independent Islamic banks had no elements of usury. Then 84.4% of sales results are getting better, 16.6% of sales results are normal. As well as 46.6% there was an increase in working capital in micro businesses, 54.4% there was no increase in capital. 33.4% of businesses run developed 66.6% of businesses run normally, 36.0% the level of income increased 16.0% the level of business income did not increase, then from 64.0% the profit from business results increased 0.4% it was normal.Keywords: Financing, sharia, business